Characterization and differentiation of aflatoxigenic species of Aspergillus section Flavi by MALDI-TOF MS - Rodrigues, Paula (2011)
Aspergillus is a large genus, with a complex taxonomy. The genus is easily identifiedd by its characteristic conidiophore, but species identification and differentiation is complex, mainly because it is traditionally based on a range of morphological features. Aspergillus subgenus Circumdati section Flavi, also refered to as the A.dflavus group, has attracted worldwide attention for its industrial use and toxigenic potential. Sectiond Flavi is divided in two groups of species. One includes the aflatoxigenic species A. flavus, A. parasiticus and A. nomius, which cause serious problems in agricultural commodities, and the other one includes the non-aflatoxigenic species A. oryzae, A. sojae and A.dtamarii, traditionally used for production of fermented foods. Species from A. flavus group are morphologically and genetically very similar, and are therefore difficult to differentiate by both cultural and molecular methods. Matrix Assisted Laser Desorption Ionization Time-of-Flight (MALDI-TOF) Massd Spectrometry has already shown high potentialities in discriminating very closely related taxa. This work intended to discriminate 30 strains, which were previously classifieddas A. flavus group by morphological methods, using MALDI-TOF MS. These results are compared with those previously obtained by conventional methods.